Reproductive disorders in female rats after prenatal exposure to betamethasone - Borges, Cibele S. [UNESP]; Pacheco, Tainá L. [UNESP]; Guerra, Marina T. [UNESP]; Barros, Aline L. [UNESP]; Silva, Patricia V. [UNESP]; Missassi, Gabriela [UNESP]; da Silva, Katiussia Pinho [UNESP]; Anselmo-Franci, Janete A.; Pupo, André S. [UNESP]; Kempinas, Wilma De G. [UNESP] (Wiley, 2017)
Betamethasone is the drug of choice for antenatal treatment, promoting fetal lung maturation and decreasing mortality. Previous studies in rats reported male programming and alteration in sperm parameters and sexual behavior following intrauterine betamethasone exposure. The impact on the female reproductive development is not known. In this study, rat female offspring was assessed for sexual development, morphophysiology of the reproductive tract and fertility after maternal exposure to 0.1 mg kg−1 of betamethasone or vehicle on gestational days 12, 13, 18 and 19. The treatment promoted reduction of litter weight on postnatal day 1, morphological masculinization in females, delay in the age of puberty onset, reduction in estrus number, increase in estrous cycle length and increase in luteinizing hormone serum levels and uterus weight. The females from the betamethasone group showed an increase of myometrial uterine area and decrease in endometrial uterine area. These animals also performed less lordosis during the sexual behavior test and showed impaired reproductive performance. The uterus showed higher contraction in the treated group as shown by a pharmacological assay. In conclusion, prenatal betamethasone exposure in rats promoted female masculinization, altered sexual development and reproductive parameters. Copyright © 2017 John Wiley & Sons, Ltd.
Keywords: betamethasone; estrous cycle; female rat; reproductive disorders; reproductive performance; sexual behavior; sexual development